Introduction to the Marine World and Coastal Engineering for Students of Athirah 2 Islamic Elementary School Makassar Through Interactive Educational Media - Hasdinar Umar; Chairul Paotonan; Achmad Yasir Baeda; Taufiqur Rachman; Sabaruddin Rahman; Ashury Djamaluddin; Firman Husain; Juswan .; Fuad Mahfud Assidiq; Andi Mega Mustika; Muhammad Fauzan A. Narayana Jufri; Andi Muhammad Ikram; Muhammad Fitrah Ramadhan Umar (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Makassar City is one of the cities with a coastal area located in its center. However, many people, especially young children, still do not understand the importance of the sea, marine technology, and its role in their lives. The low level of understanding is due to the lack of information provided about the ocean world and coastal engineering. Athirah 2 Islamic Elementary School, which is one of the partners in this community service, provides facilities for the Introduction to the Ocean World and Coastal Engineering activity. This community service activity aims to introduce the basic concepts of the ocean world and coastal engineering through a fun and interactive approach that is adapted to the age of elementary school students. This activity will be carried out in 6 sessions, namely Session 1: Opening, Introduction, and Pre-test; Session 2: Introduction to the Sea and Marine Engineering; Session 3: Simple Experiments; Session 4: Educational Games; Session 5: Reflection and Post-test; and Session 6: Closing and Documentation. After this activity is carried out, an initial awareness is formed in students about the importance of protecting the sea as part of a shared responsibility. The students were enthusiastic about learning about ocean engineering and coastal engineering, eager to learn about the ocean and coastal structures. The pre- and post-test results showed an increase in the students' understanding of ocean engineering and coastal engineering.